Field notes for the wilderness : practices for an evolving faith - Bessey, Sarah (Convergent Books, 2024)
"A nurturing and hopeful collection of practices to help an emerging generation of Christians reconnect to their faith, find inner healing, and build spiritual community-from Glennon Doyle's "favorite faith writer" and the New York Times bestselling author of Jesus Feminist and editor of A Rhythm of Prayer. It's hard to leave a faith that has raised us. Maybe it's even harder to stay. But what can feel impossible is living in the tension. Living with a faith that evolves. Sarah Bessey is an expert at faithfully stumbling forward. As a New York Times bestselling author and co-founder of Evolving Faith, the foremost community for progressive Christians, she has been trusted by thousands of people to pursue a reconstruction of faith centered on compassion, truth, and inclusion. Bessey has found a deeply underserved and underestimated remnant in the wilderness of Christianity who are still devoted to Jesus, deeply rooted in the Gospel, fascinated with Scripture, and committed to reimagining their faith. Field Notes for the Wilderness guides us through multiple principles to live by for an evolving faith, including: practicing wonder and curiosity as spiritual disciplines, mothering ourselves with compassion and empathy, making space for lament and righteous rage, finding good spiritual teachers, and discovering what we are for in this life, and moving in that direction. In this groundbreaking and nurturing book, Bessey becomes a shepherd for our curiosity, giving us a table for our questions, tools to cultivate what we crave, and a blessing for what was-even as we leave it behind"--